Crystallization and preliminary X-ray crystallographic studies of O-methyltransferase from Anabaena PCC 7120 - Li, Guoming (International Union of Crystallography, 2009)
O-Methyltransferase (OMT) is a ubiquitous enzyme that exists in bacteria, plants and humans and catalyzes a methyl-transfer reaction using S-adenosyl-l-methionine as a methyl donor and a wide range of phenolics as acceptors. To investigate the structure and function of OMTs, omt from Anabaena PCC 7120 was cloned into expression vector pET21a and expressed in a soluble form in Escherichia coli strain BL21 (DE3). The recombinant OMT protein was purified to homogeneity using a two-step strategy. Crystals of OMT that diffracted to a resolution of 2.4 Å were obtained using the hanging-drop vapour-diffusion method. The crystals belonged to space group C222(1), with unit-cell parameters a = 131.620, b = 227.994, c = 150.777 Å, α = β = γ = 90°. There are eight molecules per asymmetric unit.